Business sustainability, energy safety and environmental ethics in Chile - Suárez, Andrés (Acta Bioethica, 2013)
This paper explores the relation between business sustainability, both linked to financial profit as well as to relations with local organizations, and the environment, in a context of an internationalized economy such as the Chilean economy. Likewise, it analyzes recent conflicts originated in Chile for energy supply and the difficulties in defining an energy matrix. Finally, the article analyzes the influence of ecological ethics in the preservation of the high diversity ecosystems in the South of Chile, facing the business development and the specific energy projects.